2018
DOI: 10.1177/0271678x18803956
|View full text |Cite
|
Sign up to set email alerts
|

Small vessel disease is associated with altered cerebrovascular pulsatility but not resting cerebral blood flow

Abstract: Cerebral small vessel disease (SVD) contributes to 25% of ischemic strokes and 45% of dementias. We aimed to investigate the role of cerebral blood flow (CBF) and intracranial pulsatility in SVD. We scanned 60 patients with minor ischemic stroke, representing a range of white matter hyperintensities (WMH). We rated WMH and perivascular spaces (PVS) using semi-quantitative scales and measured WMH volume. We measured flow and pulsatility in the main cerebral vessels and cerebrospinal fluid (CSF) using phase-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
87
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 53 publications
8
87
0
1
Order By: Relevance
“…We also demonstrated that reduction in white matter CVR was associated with increased intracranial vascular pulsatility, most clearly seen in the intracranial venous sinuses and internal jugular veins, and with increased PVS visibility. (23) Importantly, we also found that reduced CVR was associated with reduced CSF stroke volume at the foramen magnum, and also that reduced CSF stroke volume was associated with increased basal ganglia PVS, showing for the first time in the intact human cranium, a possible link between dysfunctional brain interstitial fluid drainage (evidenced by increased PVS visibility) and impaired CSF pulsation (thought to help flush interstitial fluid through the glymphatic system). (30) We saw no association of reduced CVR in white or grey matter with resting CBF, or of resting CBF with any measures of SVD.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…We also demonstrated that reduction in white matter CVR was associated with increased intracranial vascular pulsatility, most clearly seen in the intracranial venous sinuses and internal jugular veins, and with increased PVS visibility. (23) Importantly, we also found that reduced CVR was associated with reduced CSF stroke volume at the foramen magnum, and also that reduced CSF stroke volume was associated with increased basal ganglia PVS, showing for the first time in the intact human cranium, a possible link between dysfunctional brain interstitial fluid drainage (evidenced by increased PVS visibility) and impaired CSF pulsation (thought to help flush interstitial fluid through the glymphatic system). (30) We saw no association of reduced CVR in white or grey matter with resting CBF, or of resting CBF with any measures of SVD.…”
Section: Discussionsupporting
confidence: 52%
“…We are the first to describe an association of increased PVS with reduced CVR and CSF stroke volume, in addition to increased intracranial vascular pulsatility. (23) Visible PVS are associated with hypertension, increasing age, systemic and intracerebral inflammation, other SVD features like WMH and microbleeds, and increased risk of dementia. (1) Longitudinal studies are required to demonstrate if PVS visibility precedes or follows impairments in CVR or changes in vascular or CSF pulsatility.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations